Experimental investigation and process simulation of the compression molding process of Sheet Molding Compound (SMC) with local reinforcements - Hohberg, Martin (Karlsruher Schriftenreihe Fahrzeugsystemtechnik, 2022)
In this book, a new three-dimensional approach for the process simulation of SMC is developed. This approach takes into account both, the core layer that is dominated by the extensional viscosity and the thin lubrication layer. In order to transfer the information from the process to the structure simulation, a CAE chain is further developed. In addition, a new rheological tool is developed to analyze flow behavior experimentally and to provide the required material parameters.